Biliary involvement in liver metastases: long-term experience with biliary biopsy from a single center - Inchingolo,Riccardo (2021)
Abstract Objective: To investigate long-term results of biliary biopsy performed with transluminal forceps in the setting of metastatic biliary involvement. Materials and Methods: Between September 2014 and June 2019, 25 patients-18 males (72%)-with a mean age of 65 ± 15 years, underwent 26 biliary biopsy procedures with a dedicated forceps system. All patients presented with obstructive jaundice that was suspected of being malignant and underwent pre-procedural magnetic resonance cholangiopancreatography. The biopsies were performed during percutaneous placement of an internal-external biliary drainage catheter, under fluoroscopic guidance. Results: The technical success rate was 96% (corresponding to 25 of the 26 procedures). The histological diagnosis was inflammatory biliary stricture in five cases, pancreatic adenocarcinoma in six, liver metastases from colorectal cancer in eight, and hepatocellular carcinoma in three, the biliary mucosa being categorized as normal in three cases. In one case, the sample was considered insufficient and the procedure was successfully repeated, after which a diagnosis of pancreatic adenocarcinoma was made. Over a follow-up period of 6-48 months, there were five false-negative results: two findings of inflammatory biliary stricture were later identified as liver metastases from breast and gastric cancer, respectively; and all three patients in which the biliary mucosa was categorized as normal were subsequently diagnosed with metastatic hilar lymph nodes. The procedure was found to have a sensitivity of 77%, a specificity of 100%, and an overall accuracy of 80%. The complication rate was 11.5% (mild, transient hemobilia occurring in three cases). Conclusion: Percutaneous transluminal forceps biopsy is a safe, effective, minimally invasive procedure for histological characterization in patients presenting with obstructive jaundice due to a non-primary biliary tumor.